PENERAPAN ASAS PACTA SUNT SERVANDA PADA TESTAMENT YANG DIBUAT DI HADAPAN NOTARIS DALAM PERSPEKTIF KEADILAN - Syaeful Bahri; Jawade Hafidz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The research entitled The Application of Pacta Sunt Servanda Principle In Testament Made Before Notary in Perspective of Justice has problem formulation: 1) How is the application of pacta sunt servanda principle on testaments made before the present notary ?, 2) What legal effect arises when The testamen made before the notary does not apply the principle of pacta sunt servanda in the perspective of justice? And 3) How is the application of pacta sunt servanda principle to testament made before Notary in the perspective of justice ?.The results of this research are 1) The application of pacta sunt servanda principle on testaments made before the present notary can be described that the implementation of pacta sunt servanda principle is required at all stages, either before, during or after the process of making the testament deed. 2) Any legal effect that arises when a testament made before a notary public does not apply the principle of pacta sunt servanda in the perspective of justice is that the testament is essentially a statement made unilaterally by the testamenter set forth in a deed that must be executed by the will . 3) The application of the principle of pacta sunt servanda to the testament made before the Notary in the perspective of justice is that in the making of this testament it must be adhered to two principles namely, firstly, giving equal rights and opportunities to the widest freedom of the broadest extent of equal freedom for each person. Second, able to reorganize the socio-economic disparities that occur so as to provide mutual benefits.Keywords: Pakta Azmen Sunt Servanda, Testament